Compatibility and enhanced eﬃcacy of mixtures of insectopathogenic fungi and neonicotinoid insecticides: an ecofriendly strategy to combat Aphis craccivora - Jaydeep Halder; Suraj Soni (Current Horticulture, 2025)
The black bean aphid, Aphis craccivora, is a sap sucking insect that feeds on leguminous vegetable crops. Both nymphs and adults suck the sap from young shoots, tender fruits, apical buds and devitalizing the plants. To control this sucking pests, diﬀerent entomopathogenic fungi, viz. Beauveria bassiana, Metarhizium anisopliae, and Lecanicillium lecanii, were tested alone and their half of their recommended doses with neonicotinoids insecticides (Imidacloprid 17.8% SL, Thiamethoxam 25% WG and Acetamiprid 20% SP) against A. craccivora during 2022 and 2023. For both consecutive years (2022 and 2023), L. lecanii had the lowest median lethal time (44.29 and 46.60 h) to kill 50% of the test population, followed by B. bassiana (45.77 and 47.89 h) and M. anisopliae (46.45 and 48.27 h). Similarly, among neonicotinoids examined, Acetamiprid was the most toxic (LT50 = 26.39 and 28.78 h). The combination of L. lecanii + Acetamiprid at half of their recommended doses was found to be the most eﬀective, leading to the lowest median lethal time of 21.85 and 22.67 h during 2022 and 2023, respectively, followed by B. bassiana + Acetamiprid (22.82 and 23.29 h). Combination of EPF like B. bassiana, M. anisopliae, and L. lecanii with neonicotinoids at half of their recommended concentrations are not only compatible but also synergistic in action and could be a viable ecofriendly option in the management of A. craccivora.